The conception of orphancy as a cultural phenomenon in the novel “Tsar maiden” by Vsevolod Solovyov - Lyapina Svetlana Mitrofanovna (Studia Humanitatis, 2014)
The article analyses a little-known novel “Tsar Maiden” by Vsevolod Solovyov from the point of view of its motive structure. Еhe author places special emphasis on the motive of orphancy. This angle shows the images of the lead characters, tzarevna Sophia Romanova and a provincial noblewoman Lyuba Kadasheva. On the one hand, orphancy becomes the source of spiritual development (Lyuba). On the other hand, it leads to exasperation and moral degradation (Sophia).